PENGEMBANGAN KOPI CIWALUH UNTUK MEMPERKUAT DAYA TARIK WISATA DAN PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA WISATA PASIR BUNCIR - Rilla Rianty; Regina Dewi Hanifah; Antonius Rizki Krisnadi (Jurnal Terapan Abdimas, 2026)
Abstract. Pasir Buncir Tourism Village in Bogor Regency has considerable agro-ecotourism potential supported by Ciwaluh Coffee as a distinctive local product. However, this potential has not been fully utilized as a tourism attraction due to weak product branding, limited digital marketing, inadequate community capacity, and the lack of integration of coffee into educational tourism activities. This community service program aimed to develop Ciwaluh Coffee as a tourism attraction while strengthening community-based economic empowerment. The program was conducted on 9 May 2026 and involved 30 participants, including members of the Tourism Awareness Group (Pokdarwis), coffee MSME owners, coffee farmers, and local residents. The program adopted a participatory community empowerment approach through observation, focus group discussions, socialization, training, hands-on practice, and mentoring. The results demonstrated the development of an initial community-based coffee educational tourism concept, preliminary product identity and packaging designs for Ciwaluh Coffee, and sample digital promotional content for social media. The program also enhanced participants' basic knowledge and practical skills in product branding, digital marketing, and coffee educational tourism development. Overall, the program established an initial foundation for community-based coffee tourism development by strengthening local capacity, reinforcing product identity, and integrating Ciwaluh Coffee into sustainable tourism development in Pasir Buncir Tourism Village.   Abstrak. Desa Wisata Pasir Buncir, Kabupaten Bogor, memiliki potensi agroekowisata yang didukung oleh Kopi Ciwaluh sebagai produk unggulan masyarakat. Namun, potensi tersebut belum dimanfaatkan secara optimal sebagai daya tarik wisata karena lemahnya branding produk, keterbatasan pemasaran digital, rendahnya kapasitas sumber daya manusia, serta belum terintegrasinya kopi ke dalam atraksi wisata edukasi. Kegiatan pengabdian kepada masyarakat ini bertujuan mengembangkan Kopi Ciwaluh sebagai penguat daya tarik wisata sekaligus instrumen pemberdayaan ekonomi masyarakat. Kegiatan dilaksanakan pada 9 Mei 2026 dengan melibatkan 30 peserta yang terdiri atas anggota Pokdarwis, pelaku UMKM kopi, petani kopi, dan masyarakat setempat. Metode yang digunakan adalah participatory community empowerment melalui observasi, diskusi kelompok terarah, sosialisasi, pelatihan, praktik langsung, dan pendampingan. Hasil kegiatan menunjukkan tersusunnya konsep awal wisata edukasi kopi, rancangan identitas dan kemasan produk Kopi Ciwaluh, serta contoh konten promosi digital berbasis media sosial. Kegiatan juga meningkatkan pemahaman dan keterampilan dasar peserta dalam branding, pemasaran digital, dan pengembangan wisata edukasi kopi. Program ini menghasilkan fondasi awal pengembangan wisata kopi berbasis masyarakat melalui penguatan kapasitas masyarakat, identitas produk, dan integrasi Kopi Ciwaluh sebagai daya tarik Desa Wisata Pasir Buncir yang berkelanjutan.